Incidence and associated risk factors of uterine prolapse in dairy cows in Manoharganj Upazila, Cumilla District, Bangladesh - Wasef, Al; Uday Kumar Mohanta; Sah, Vijay Kumar; Islam, Md. Rashedul; Khadka, Nita; Budhathoki, Nabina; Islam, Md. Shakil (Universitas Airlangga, 2025)
Uterine prolapse is a medical emergency in cows that can be life-threatening if not promptly treated. This study aimed to determine the incidence, associated risk factors, survival rate, conception rate, and management practices related to uterine prolapse in dairy cows in Manoharganj Upazila, Cumilla District, Bangladesh. Data collected from cow owners were analyzed using the Chi-square test. A total of 102 cases of uterine prolapse were manually corrected. The incidence was found to be higher in crossbred (61.76%) compared to local (38.24%) cows. Similarly, cows that were artificially inseminated showed a significantly higher incidence (93.14%) than those bred naturally (6.86%). Pluriparous cows had a greater incidence (77.45%) than primiparous cows (22.55%). Additionally, cows with a previous history of vaginal prolapse (48.04%) or dystocia (59.80%) were more likely to experience uterine prolapse than those without such histories. Following treatment, 91.18% of the affected cows survived, while 8.82% died. Among the survivors, 15.05% were culled, and the remaining cows were artificially inseminated of which 82.27% successfully conceived. The study also observed that 3.92% of cows were diagnosed with hypocalcemia shortly after prolapse correction. These findings highlight the importance of immediate veterinary intervention and the need for proper nutritional management during pregnancy to help prevent uterine prolapse.